2021
DOI: 10.1111/nph.17643
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for selectively constrained 3D flower shape evolution in a Late Miocene clade of Malagasy Bulbophyllum orchids

Abstract: Summary Questions concerning the evolution of complex biological structures are central to the field of evolutionary biology. Yet, still little information is known about the modes and temporal dynamics of three‐dimensional (3D) flower shape evolution across the history of clades. Here, we combined high‐resolution X‐ray computed tomography with 3D geometric morphometrics and phylogenetic comparative methods to test models of whole‐flower shape evolution in the orchid family, using an early Late Miocene clade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 123 publications
(230 reference statements)
0
21
0
Order By: Relevance
“…In fact, the floral primordial initiation of the labellum usually follows immediately after the development of the lateral petals (e.g., in Phalaenopsis: 4). Notably, in a previous study by Artuso et al (2021), the OU model was found to best explain whole-flower shape variation among Bulbophyllum Clade A species and interpreted to reflect pollinator-driven (directional and/or stabilizing) selection (see also Serrano-Serrano et al 2015;Joly et al 2018;Ibañez et al 2019;Reich et al 2020). In consequence, based on the present results, the same selective pressures might be invoked for sepals, lateral petals, and labellum + column-foot.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…In fact, the floral primordial initiation of the labellum usually follows immediately after the development of the lateral petals (e.g., in Phalaenopsis: 4). Notably, in a previous study by Artuso et al (2021), the OU model was found to best explain whole-flower shape variation among Bulbophyllum Clade A species and interpreted to reflect pollinator-driven (directional and/or stabilizing) selection (see also Serrano-Serrano et al 2015;Joly et al 2018;Ibañez et al 2019;Reich et al 2020). In consequence, based on the present results, the same selective pressures might be invoked for sepals, lateral petals, and labellum + column-foot.…”
mentioning
confidence: 86%
“…S1). Phylogenetic half-lives are usually interpreted as the average time it takes a species to evolve halfway from its ancestral state (here: module shape) toward the optimum (see also Artuso et al 2021), thereby indicating the strength of the OU process acting on the species. When α is zero and/or t 1/2 is larger relative to tree height, the OU model collapses to the BM model (Beaulieu et al 2012;Cooper et al 2016).…”
Section: Testing Modes and Rates Of Module Evolutionmentioning
confidence: 99%
See 3 more Smart Citations